The emergence of neuromarketing investigated through online public communications (2002–2008). Issue 3 (2nd March 2021) - Levallois, Clement; Smidts, Ale; Wouters, Paul
Abstract: 'Neuromarketing' designates both a developing industry and an academic research field. This study documents the emergence of neuromarketing through the first mention of the term in traditional and new media until the stabilization of the field. Our main interest is to establish whether neuromarketing developed separately as an academic field and as an industry (with knowledge transfer from the former to the latter), or whether it was an act of co-creation. Based on a corpus gathered from a systematic search on the Web, we trace the multiple forms of engagement between academic and commercial communities, echoed but also shaped by reports in traditional and new media. We find that neuromarketing developed an identity through a set of practices and a series of debates which involved intertwined communities of academic researchers and practitioners. This result offers an alternative to the narrative of 'knowledge transfer' between academia and the industry and offers a contribution on how to use new kinds of digital sources in business history.